2018
DOI: 10.1145/3145846
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Assessment Framework for Mobile-Based Emergency Intervention Apps

Abstract: Smartphone applications to support healthcare are proliferating. A growing and important subset of these apps supports emergency medical intervention to address a wide range of illness-related emergencies to speed the arrival of relevant treatment. The emergency response characteristics and strategies employed by these apps are the focus of this study, resulting in an mHealth Emergency Strategy Index. While a growing body of knowledge focuses on usability, safety, and privacy aspects that characterize such app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…For example, Stoyanov and colleagues [ 25 ] developed a scale to classify and rate the quality of mHealth apps. There have also been other attempts to provide alternatives for assessing mHealth apps (eg, [ 26 , 27 ]), each one of which suggests its own quality criteria. All these attempts have positive and negative characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Stoyanov and colleagues [ 25 ] developed a scale to classify and rate the quality of mHealth apps. There have also been other attempts to provide alternatives for assessing mHealth apps (eg, [ 26 , 27 ]), each one of which suggests its own quality criteria. All these attempts have positive and negative characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…All these attempts have positive and negative characteristics. A major limitation common to many of these initiatives is that they have been created from one narrow perspective and focusing on, for example, a specific health problem or intervention such as emergency interventions [ 27 ] or a stakeholder such as adolescents [ 26 ]. In addition, some of them have been created from a specific perspective, for example, taking into account usability issues rather than safety.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that nearby patient-peers who maintain long-term EAI prescriptions can potentially deliver their personal EAI to the patient in need through a proximity-based emergency response communities (ERC) app [8,9]. As described in Figure 1, ERC apps dispatch nearby registered patients with allergy to help a patient in immediate need of an EAI, in certain configurations following the approval of EMS.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple apps exist in this area, such as Pulsepoint [43], Allergy-Hero [44], and UnityPhilly [45]. An extensive review of emergency response apps can be found in the study by Gaziel-Yablowitz and Schwartz [46].…”
Section: Good Samaritan Response By Medical Professionalsmentioning
confidence: 99%